ANALYSIS OF ULTRAHSORT LASER PULSES PROPAGATION IN MEDIUM: LITHARGE GLASS SF56A - Mounir, Khelladi (International Journal of Research -GRANTHAALAYAH, 2019)
Propagation of an ultra-short lasers pulses in a linear optical medium consisting of free space, dispersive media. However, analytical methods have the limitations of not being able to handle arbitrary pulse profiles. Also, closed form solutions are often obtained after certain levels of approximations. This has motive a few studies based on the use of numerical simulation techniques in the analysis of pulse propagation. In view of the recent advance in ultra-short pulse propagation, a strong need is felt for developing a numerical formalism capable of performing such a complete analysis of the issues involved in pulse propagation. This allows us to analyze the pulse in the time-frequency domain at any arbitrary plane. With this tool, we investigate the spectral and temporal evolution of ultra-short pulses at any arbitrary propagation distance.